What it is like to go to war [compact disc, unabridged] - Marlantes, Karl (Blackstone Audio, Inc., 2011)
In his memoir, Marlantes relates his combat experiences in Vietnam and discusses the daily contradictions warriors face in the grind of war, where each battle requires them to take life or spare life. He also underscores the need for returning veterans to be counseled properly.